1970
DOI: 10.3126/saarctb.v8i1.5885
|View full text |Cite
|
Sign up to set email alerts
|

Study On The Prevalence Of Pulmonary Tuberculosis Among Hiv Positive Attending Hiv Clinics In Eastern Nepal

Abstract: Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. More than 2 billion people are infected with TB bacilli worldwide. It is a leading public health problem particularly in the developing countries. The HIV epidemic has increased the global tuberculosis burden. TB is the commonest opportunistic infection and leading cause of mortality of People living with HIV (PLHA). Tuberculosis is a major public health problem in Nepal. The objective of the study is to determine prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
2
6
1
Order By: Relevance
“…This finding was in line with studies conducted in India (17%), Nigeria (16.8%, 14.4%, 9.6% [1][2][3][4]. However, relatively higher prevalence has been reported from Nepal (27.3%) and Nigeria (22.7%) [5,6], and lower results were reported from Northern Tanzania (8.3%) [7]. Slight variation on the magnitude of tuberculosis in HIV/AIDS patients may be due to differences of HIV infection rate in the population, TB-diagnostic facilities available, health care awareness of the community to seek health care for both TB and HIV.…”
Section: Discussionsupporting
confidence: 75%
“…This finding was in line with studies conducted in India (17%), Nigeria (16.8%, 14.4%, 9.6% [1][2][3][4]. However, relatively higher prevalence has been reported from Nepal (27.3%) and Nigeria (22.7%) [5,6], and lower results were reported from Northern Tanzania (8.3%) [7]. Slight variation on the magnitude of tuberculosis in HIV/AIDS patients may be due to differences of HIV infection rate in the population, TB-diagnostic facilities available, health care awareness of the community to seek health care for both TB and HIV.…”
Section: Discussionsupporting
confidence: 75%
“…Yadav DK et al revealed that majority of HIV positive subjects are in the age group of 30-39 years (48.8%). 33 Our study shows that maximum number (40.90%) of TB-HIV co-infected positive patients were from 25 to 34 years of age group. After that 36.36% of patients were from age group of 35 to 49 years.…”
mentioning
confidence: 52%
“…32 Yadav DK et al showed the proportion of females amongst the HIV positives of 24.8%. 33 Our study reveal that maximum number of HIV positive patients 69(41.32%) were from 25 to 34 years of age. Yadav DK et al revealed that majority of HIV positive subjects are in the age group of 30-39 years (48.8%).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…3 According to South Asian Association For Regional Co-orporation (SAARC) Tuberculosis and HIV/ AIDS centre, in the year 2011, the prevalence of TB was 352 per lakh in Afghanistan, 411 per lakh in Bangladesh, 177 per lakh in Bhutan, 249 per lakh in India, 33 per lakh in Maldives, 238 per lakh in Nepal, 350 per lakh in Pakistan and 101 per lakh in Srilanka. 4 TB is a major public health problem in Nepal. Despite the remarkable progress made by National Tuberculosis Program (NTP) since 2006, the disease still remains a threat in Nepal.…”
Section: Introductionmentioning
confidence: 99%